دراسة تحليلية عن كتاب "امثلتي 5" للحاج توفق الحكيم - jamaluddin shiddiq; ummul ma'rifah (Imtiyaz : Jurnal Pendidikan dan Bahasa Arab, 2019)
AbstractThe purpose of this study was to find out: the presentation of the book Amtsilatipart 5 by Haj Tawfiq al-Hakim and the presentation the methodevaluation of it. This research is a type of library research. The results of this study are: (1) In terms of presentation of material, the material chosen is in accordance with the learning objectives. In terms of the level of ability of students, this book is suitable to be taught to elementary level students. As for the ease of learning, there are significant problems, namely the example from the Qur'an will be difficult for non-Arabic students. Besides the material, this book uses two examples of gradations, namely collective gradations and sequential gradations. In presenting materials, this book uses three procedures: priority procedures, drawing procedures, and context procedures. As for the addition of the presentation, it was considered not good. For material review, this book contains several exercises for material repetition.(2) In terms of evaluation, amtsilati 5 uses a type of formative structural evaluation. Various forms of evaluation are used, such as form training, word composing exercises, word completing exercises, application exercises, repetition training and meaning giving exercises.